Chitin, chitosan, oligosaccharides and their derivatives : biological activities and applications - Kim, Se-Kwon (Taylor & Francis [distributor], 2011)
Biopolymers found in marine animals and plants offer tremendous, largely untapped pharmaceutical potential. This book covers the key aspects of these therapeutically valuable biopolymers and their derivatives, namely, their properties, sources, production, and applications in food science and technology as well as biological and biomedical fields